The psychological assessment of clerics - Jack, Alexander; Wilcox, Daniel T. (Springer, 2017)
The psychological assessment of novice and experienced clerics is an important component of ordination, suitability, and risk evaluation to ensure that representatives of religious organizations are equipped, motivated, and safe for a life commitment to a faith vocation. It is the authors’ opinion that such assessments should be conducted by skilled psychologists with expertise that covers occupational, clinical, and forensic domains. Further, the authors emphasize the importance of an objective and secular assessment to better inform the church.